Dopamine versus norepinephrine in the treatment of cardiogenic shock: A PRISMA-compliant meta-analysis. Issue 43 (October 2017) - Rui, Qing; Jiang, Yufeng; Chen, Min; Zhang, Nannan; Yang, Huajia; Zhou, Yafeng
Abstract: Background: Guidelines recommend that norepinephrine (NA) should be used to reach the target mean arterial pressure (MAP) during cardiogenic shock (CS), rather than epinephrine and dopamine (DA). However, there has actually been few studies on comparing norepinephrine with dopamine and their results conflicts. These studies raise a heat discussion. This study aimed to validate the effectiveness of norepinephrine for treating CS in comparison with dopamine. Methods: We performed a meta-analysis of randomized controlled trials (RCTs) to assess pooled estimates of risk ratio (RR) and 95% confidence interval (CI) for 28-day mortality, incidence of arrhythmic events, gastrointestinal reaction, and some indexes after treatment. Results: Compared with dopamine, patients receiving norepinephrine had a lower 28-day mortality (RR 1.611 [95% CI 1.219–2.129]; P < .001; P heterogeneity = .01), a lower risk of arrhythmic events (RR 3.426 [95% CI 2.120–5.510]; P < .001; P heterogeneity = .875) and a lower risk of gastrointestinal reaction (RR 5.474 [95% CI 2.917–10.273]; P < .001; P heterogeneity = 0). In subgroup analyses on 28-day mortality by causes of CS, there were more benefits from norepinephrine than dopamine in 2 subgroups. Conclusions: Our analysis revealed that norepinephrine was associated with a lower 28-day mortality, a lower risk of arrhythmic events, and gastrointestinal reaction. No matter whether CS is caused by coronary heart disease or not, norepinephrine is superior to dopamine for correcting CS on the 28-day mortality. Abstract : Supplemental Digital Content is available in the text